By limit process, the derivative of a function f(x) is :-

f'(x) = lim h --> 0 [{f(x+h) - f(x)}/h]

Now, the given function is :-

f(x) = sqrt(x+4)

THus, f'(x) = lim h --> 0 [{f(x+h) - f(x)}/h]

or, f'(x) = lim h ---> 0 [{(sqrt(x + h+ 4)) - sqrt(x+4)}/h]

rationalizing the numerator we get

f'(x) = lim h ---> 0

[{(sqrt(x + h+ 4)) - sqrt(x+4)}*{(sqrt(x + h+ 4)) + sqrt(x+4)}/{h*{(sqrt(x + h+ 4)) + sqrt(x+4)}}]

or, f'(x) = lim h ---> 0 [{(x+h+4) - (x+4)}/{h*{(sqrt(x + h+ 4)) + sqrt(x+4)}}]

or, f'(x) = lim h ---> 0 [h/{h*{(sqrt(x + h+ 4)) + sqrt(x+4)}}]

or, f'(x) = lim h ---> 0 [1/{1{(sqrt(x + h+ 4)) + sqrt(x+4)}}]

putting the value of h = 0 in the above expression we get;

f'(x) = 1/{2*sqrt(x+4)}

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now